The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18786/2072-0505-2019-47-022
|View full text |Cite
|
Sign up to set email alerts
|

Mixed connective tissue disease, undifferentiated connective tissue disease and overlap syndromes

Abstract: Systemic lupus erythematosus, systemic sclerosis, inflammatory myopathy and rheumatoid arthritis are systemic connective tissue disorders which are characterized by heterogeneous clinical symptoms and variable course. To date, updated diagnostic criteria for early diagnosis of each of the diseases of this group have been proposed. At the same time, a proportion of patients already have at the onset of the disease or over time, a combination of signs characteristic of different diseases. Such conditions are ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(51 reference statements)
0
0
0
3
Order By: Relevance
“…In our cohort, anemia was found in 38(74.5%), leukopenia in 2 (3.9%), and thrombocytopenia in 3(5.8%) patients, while according to Alek, hematologic abnormalities are often seen in patients. They may have anemia, as well as leukopenia, lymphopenia, and thrombocytopenia, as observed (Alekperov, 2019).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In our cohort, anemia was found in 38(74.5%), leukopenia in 2 (3.9%), and thrombocytopenia in 3(5.8%) patients, while according to Alek, hematologic abnormalities are often seen in patients. They may have anemia, as well as leukopenia, lymphopenia, and thrombocytopenia, as observed (Alekperov, 2019).…”
Section: Resultsmentioning
confidence: 96%
“…In our study MCTD 33(73.3%), SSc-SLE overlap were 3(6.7%), SSc-myositis were 2(3.9% reported that in about 20% of MCTD patients, the clinical features evolved to another CTD over 5 years. In 50% of patients, the disease evolved similarly over 10 years (Alekperov, 2019). Anti-DNA antibodies were found in the MCTD patients with evolution into SLE.…”
Section: Resultsmentioning
confidence: 97%
“…Однако бывают случаи, когда у пациента не наблюдают достаточный набор критериев, необходимых для определения диагноза, или имеются признаки двух и более системных заболеваний соедини-/ 2020 / ТОМ 19 / № 3 CURRENT PEDIATRICS / 2020 / V. 19 / № 3 тельной ткани. В таких случаях формулируют диагноз «Недифференцированное заболевание соединительной ткани», «Смешанное заболевание соединительной ткани» или «Перекрестный синдром» [1].…”
Section: обоснованиеunclassified
“…Характерной особенностью этого заболевания является наличие антител -анти-U1-РНП. Необходимо отметить, что анти-U1-РНП обнаруживают в 95-100% случаев при смешанном заболевании соединительной ткани, в 13-44% -при системной красной волчанке, в 5-30% -при системной склеродермии и в 10% -при ревматоидном артрите [1,15]. У описываемой нами пациентки был диагностирован высокий титр данных антител.…”
Section: клинический диагнозunclassified
See 1 more Smart Citation